1987
DOI: 10.1210/jcem-64-5-1054
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Corticotropin-Releasing Hormone Concentrations During Pregnancy and Parturition*

Abstract: Plasma CRH was measured in maternal plasma throughout the third trimester of pregnancy, during labor, and postpartum. CRH levels were also measured in arterial and venous umbilical cord plasma samples. In normal pregnant women, plasma CRH increased from 50 +/- 15 (+/- SEM) pg/mL at 28 weeks gestation (n = 41) to 1462 +/- 182 pg/mL at 40 weeks (n = 55) and 1680 +/- 101 pg/mL (n = 65) in labor. Women with pregnancy-induced hypertension (n = 49) had plasma CRH levels significantly elevated above this normal range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
168
3
7

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(192 citation statements)
references
References 19 publications
14
168
3
7
Order By: Relevance
“…CRH concentrations were the same in both groups and much lower than before delivery. Some investigators found rising CRH levels during term labour (9, 10); others reported no change in plasma CRH as labour progressed (11,12). In all of these studies CRH concentration was measured at the second stage of delivery, whereas we measured its level after delivery of the placenta.…”
Section: Discussionmentioning
confidence: 97%
“…CRH concentrations were the same in both groups and much lower than before delivery. Some investigators found rising CRH levels during term labour (9, 10); others reported no change in plasma CRH as labour progressed (11,12). In all of these studies CRH concentration was measured at the second stage of delivery, whereas we measured its level after delivery of the placenta.…”
Section: Discussionmentioning
confidence: 97%
“…In human pregnancy, the placenta releases CRH and maternal plasma CRH levels increase exponentially, peaking at delivery, and returning to pre-pregnancy levels within 24 hours of birth (Campbell et al, 1987, Kalantaridou et al, 2004. Interestingly, placental production of CRH seems to occur only in primate species, again reinforcing the uniqueness of human parturition (Robinson et al, 1989).…”
Section: Corticotropin-releasing Hormone and The "Placental Clock"mentioning
confidence: 99%
“…This strongly suggested an alternative, non-hypothalamic origin of irCRF-41 present in the systemic circulation. Multiple sources of peripheral irCRF-41 may be Postulated on the basis of immunohistochemical or content studies (18)(19)(20)(21)(22)(23)(24). Of particular interest were the adrenal glands, which contain and secrete CRF-like immunoreactivity (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories have reported the presence of irCRF-41 in human or rat peripheral plasma (10)(11)(12)(13)(14)(15)(16)(17). During pregnancy, peripheral irCRF-41 appears to be derived from the placenta (18)(19)(20). The source of peripheral irCRF-41 in non-pregnant animals is unknown and it has been postulated that it may reflect, at least in part, hypothalamic irCRF-41 secretion (13,14,16,17); other sources include the gastrointestinal tract (21), the pancreas (22) and the adrenal gland (23,24).…”
mentioning
confidence: 99%